ANALYSIS OF THE DEVELOPMENT OF PUBLIC SERVICE MALL ON THE DEVELOPMENT OF SPECIAL ECONOMIC ZONES IN KENDAL REGENCY - Dessy Mayasari (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The presence of the Public Service Mall (MPP) in Kendal Regency was developed as an effort to encourage licensing services and increase investment as an effort to realize special economic zone development policies such as strengthening the MSME sector, tourism investment and strengthening investment in the Kendal Industrial Estate. The purpose of this study is to analyze the effect of the development of the Public Service Mall (MPP) on the strengthening of special economic zones in the industrial and service sectors in Kendal Regency. The research method used in this study is the mix method, which quantitatively uses linear regression analysis to determine the effect of the Public Service Mall (MPP) on strengthening the development of special economic zones in Kendal Regency, qualitative analysis is carried out to determine the role of MPP in improving public services. The results of this study indicate that the Public Service Mall (MPP) has a significant effect on strengthening the Special Economic Zone (SEZ) in Kendal Regency. These results are in line with the qualitative analysis of the role of the Public Service Mall (MPP) on public services in Kendal Regency which plays a good role.